Electrophysiology in the time of coronavirus: coping with the great wave. Issue 12 (30th September 2020) - Li, Jia; Mazzone, Patrizio; Leung, Lisa W M; Lin, Weiqian; D'Angelo, Giuseppe; Ma, Jun; Li, Jin; Akhtar, Zaki; Li, Yuechun; Della Bella, Paolo; Lin, Jiafeng; Gallagher, Mark M
Abstract: Aims : To chart the effect of the COVID-19 pandemic on the activity of interventional electrophysiology services in affected regions. Methods and results : We reviewed the electrophysiology laboratory records in three affected cities: Wenzhou in China, Milan in Italy, and London in the UK. We inspected catheter lab records and interviewed electrophysiologists in each centre to gather information on the impact of the pandemic on working patterns and on the health of staff members and patients. There was a striking decline in interventional electrophysiology activity in each of the centres. The decline occurred within a week of the recognition of widespread community transmission of the virus in each region and shows a striking correlation with the national figures for new diagnoses of COVID-19 in each case. During the period of restriction, workflow dropped to <5% of normal, consisting of emergency cases only. In two of three centres, electrophysiologists were redeployed to perform emergency work outside electrophysiology. Among the centres studied, only Wenzhou has seen a recovery from the restrictions in activity. Following an intense nationwide programme of public health interventions, local transmission of COVID-19 ceased to be detectable after 18 February allowing the electrophysiology service to resume with a strict testing regime for all patients. Conclusion : Interventional electrophysiology is vulnerable to closure in times of great social difficulty including the COVID-19 pandemic. Intense public health intervention can permit suppression of local disease transmission allowing resumption of some normal activity with stringent precautions. Graphical abstract: